2015
DOI: 10.1186/s12909-015-0468-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of peer role play and standardized patients in undergraduate communication training

Abstract: BackgroundThe few studies directly comparing the methodological approach of peer role play (RP) and standardized patients (SP) for the delivery of communication skills all suggest that both methods are effective. In this study we calculated the costs of both methods (given comparable outcomes) and are the first to generate a differential cost-effectiveness analysis of both methods.MethodsMedical students in their prefinal year were randomly assigned to one of two groups receiving communication training in Pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 28 publications
3
52
2
1
Order By: Relevance
“…[15][16][17][18] The differences between the measures used in this study versus previous research may help explain the differences. Further, the students in this study participated in five cases over five weeks.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…[15][16][17][18] The differences between the measures used in this study versus previous research may help explain the differences. Further, the students in this study participated in five cases over five weeks.…”
Section: Discussioncontrasting
confidence: 48%
“…In contrast to the Bosse and colleagues study, which showed that RP led to better student outcomes than SP, our intervention consisted of one topic over the course of 5 weeks compared to nine cases covering multiple aspects of communication over a period of 3 weeks. 17 Another difference between our study and the Bosse study is the use of the modified Angoff method in the current study to establish a minimum level of competency via a cut-score. The Bosse and colleagues study did not state whether an attempt was made to establish a minimum competency score, which also may explain the differences in the conclusions between the studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[44][45][46] In addition, this simulation modality can be initiated without requiring a huge amount of resources and is thus relatively cost-effective. [47] To evaluate whether the training program managed to meet the intended training objectives, participants were asked after each respective simulation session what they considered were the main lessons learned. According to trainees, overall learning outcomes were two-fold.…”
Section: Discussionmentioning
confidence: 99%